Проектирование мультисервисной телекоммуникационной системы NGN согласно критерию максимума прибыли оператора связи - Агеев, Д. В. (Eastern-European Journal of Enterprise Technologies, 2020)
Maximum profit of telecommunication provider criteria usage is offered for multiservice telecommunication systems design. In the given article descripted mathematical model and problem definition for telecommunication system structure and parametrical synthesis